Stein and Heidegger – Two Phenomenologies - Szulc, Aleksandra (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
The main aim of this article is to explain Heidegger’s and Stein’s conception of phenomenology. These analyses provide a basis for an attempt to explain Stein’scritique of Heidegger’s thought. First, I present Heidegger’s phenomenology, which can be described as hermeneutic, that is to say his conception assumes an understanding of being as a fundamental category. Next, I introduce Stein’s personal phenomenology, termed as such because her explorations focus on human being. In the last part of my paper, I show how Stein considers the incompleteness of Heidegger’s analysis of Dasein,death and temporality as the main shortcomings of his thought. Stein accuses Heideggerof saying nothing about the possibility of eternity and takes into account only finite existence.My interpretation is that Stein’s appraisal, in the main, stems from her understanding of phenomenology which differs from Heidegger’s.